Manganese zinc ferrite laminated sintering method

The manganese-zinc ferrite laminate sintering method uses a coated zirconium oxide powder mixture and a two-stage sealed sintering process to prevent adhesion and deformation, enhancing yield and product quality by improving coating adhesion and surface texture.

CN119219422APending Publication Date: 2024-12-31BEIJING QIXING FEIXING ELECTRONICS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411261001.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the traditional sintering process of manganese-zinc ferrite, the blanks tend to stick and deform due to impurities and polyvinyl alcohol not volatilizing, leading to reduced yield and product quality.

Method used

A manganese-zinc ferrite laminate sintering method involving the use of a mixed liquid composed of zirconium oxide powder with specific additives, applied as a coating on the blanks, followed by a two-stage sintering process in a sealed environment to prevent adhesion and deformation.

Benefits of technology

The method effectively prevents sticking and deformation, improving yield and product quality by maintaining the coating on the surface and enhancing adhesion, resulting in a rough surface texture that enhances coating adhesion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a manganese zinc ferrite laminated sintering method which comprises the following steps: S1, mixing zirconium oxide powder and water uniformly to obtain a mixed solution; the mass fraction of the zirconium oxide powder in the mixed solution is 15-30%, and the zirconium oxide powder comprises the following components: zirconium oxide, yttrium oxide, magnesium oxide, polyvinyl alcohol, carboxymethyl cellulose, ammonium polyacrylate, sodium hexametaphosphate, a plasticizer and a lubricant; s2, tidily stacking more than one layer of manganese zinc ferrite blanks up and down on a load bearing plate, wherein at least the upper surfaces of the manganese zinc ferrite blanks in each layer are coated with a mixed solution; then putting the setter plate and the manganese zinc ferrite blank loaded on the setter plate into sintering equipment for close-packed sintering to obtain a semi-finished product; and S3, grinding the semi-finished product, cleaning, and airing to obtain a manganese zinc ferrite finished product. And adhesion deformation of the blank in the sintering process is avoided, and the yield is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic material production, in particular to a manganese-zinc ferrite laminated sintering method. Background Art

[0002] Soft ferrite cores are important basic functional components in the electronic information industry, such as power supplies, communications, electric light sources, smart home appliances, etc. They are also the most diverse, widely used, and largest-volume magnetic components. After more than half a century of development and innovation, the performance of soft ferrites has been greatly improved and enhanced worldwide, and its output has increased year by year, with its application areas and scope expanding.

[0003] At present, in the production process of soft ferrites, powder preparation, molding and sintering are the main production processes, among which sintering is the key process. The deformation and quality requirements of soft ferrite products are very strict, and product deformation is an important factor affecting product size and quality. In the traditional sintering process, ferrite blanks are directly stacked on the support plate for sintering, and a close-packed sintering method is generally adopted, and nothing is sprinkled between the blanks; because the blanks are closely packed, impurities and polyvinyl alcohol are not easy to volatilize during the sintering process, and the blanks are easy to stick, resulting in adhesion and deformation of the final product, reducing the pass rate and affecting product quality.

[0004] Manganese-zinc ferrite (Mn-Zn Fe2O4) is a common type of soft ferrite with high magnetic permeability, low loss and high resistivity. It is mainly used in electronic devices such as inductors, transformers, magnetic rings and RF suppression.

[0005] Therefore, an improved manganese-zinc ferrite laminate sintering method is urgently needed. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for sintering a manganese-zinc ferrite laminate, during which the blank will not be adhered or deformed, and the yield rate is high.

[0008] (II) Technical solution

[0009] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0010] The present invention provides a manganese-zinc ferrite laminate sintering method, comprising the following steps:

[0011] S1. Mixing zirconium oxide powder and water to obtain a mixed solution after mixing evenly; the mass fraction of zirconium oxide powder in the mixed solution is 15% to 30%, and the components of zirconium oxide powder include zirconium oxide, yttrium oxide, magnesium oxide, polyvinyl alcohol, carboxymethyl cellulose, ammonium polyacrylate, sodium hexametaphosphate, plasticizer and lubricant;

[0012] S2, stacking the manganese-zinc ferrite blanks neatly up and down in one layer or more on the setter plate, wherein at least the upper surface of the manganese-zinc ferrite blanks in each layer is coated with the mixed liquid; then placing the setter plate and the manganese-zinc ferrite blanks carried thereon into a sintering device for close-packed sintering to obtain a semi-finished product;

[0013] S3, grinding the semi-finished product, cleaning and drying it to obtain a manganese-zinc ferrite finished product;

[0014] Among them, the close-packed sintering is divided into two stages. In the first stage, the temperature is increased to 700-800°C at a heating rate of 5-10°C / min, and the sintering process is a fully open environment or an exhaust environment. In the second stage, the temperature is increased to 1300-1400°C at a heating rate of 80-90°C / min, and then kept warm for 280-330 minutes. The sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment.

[0015] Optionally, the components of the zirconium oxide powder include, by mass percentage, 70% to 90% zirconium oxide, 5% to 15% yttrium oxide, 1% to 5% magnesium oxide, 1% to 5% polyvinyl alcohol, 0.5% to 3% carboxymethyl cellulose, 0.1% to 2% ammonium polyacrylate, 0.1% to 1% sodium hexametaphosphate, 0.5% to 3% plasticizer, and 0.1% to 2% lubricant.

[0016] Optionally, the components of the zirconium oxide powder include, by mass percentage, 75% to 86% zirconium oxide, 6% to 10% yttrium oxide, 1% to 3% magnesium oxide, 2% to 3% polyvinyl alcohol, 1.2% to 3% carboxymethyl cellulose, 0.9% to 1.5% ammonium polyacrylate, 0.6% to 1% sodium hexametaphosphate, 0.7% to 2% plasticizer, and 0.3% to 1.3% lubricant.

[0017] Optionally, in S2, the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid, and the coating method is: the manganese-zinc ferrite blanks are placed close to each other on the supporting plate, and after each layer is placed, a layer of the mixed liquid is brushed on the upper surface of the manganese-zinc ferrite blanks in that layer.

[0018] Optionally, in S2, all surfaces of the manganese-zinc ferrite blanks in each layer are coated with the mixed liquid, and the coating method is: immersing the manganese-zinc ferrite blanks in the mixed liquid and then taking them out to obtain manganese-zinc ferrite blanks coated with the mixed liquid, placing the manganese-zinc ferrite blanks coated with the mixed liquid close to each other on a supporting plate, and neatly stacking the manganese-zinc ferrite blanks up and down in more than one layer.

[0019] Optionally, the manganese-zinc ferrite laminate sintering method further includes: S4, applying a coating layer to the surface of the manganese-zinc ferrite finished product, and then performing a curing treatment to obtain a coated ferrite.

[0020] Optionally, in S2, the sintering temperature is 1300-1400° C., and the sintering time is 280-330 min.

[0021] Optionally, the manganese-zinc ferrite blank has a ring shape, an EE shape, a PQ shape or a pot shape.

[0022] Optionally, the components of the manganese-zinc ferrite blank include a main component and additives; the main components include Fe2O3, Mn3O4, NiO and ZnO. Based on the amount of the main components, the content of Fe2O3 in the main components is 50-60 mol%, the content of Mn3O4 is 10-16 mol%, the content of NiO is 20-28 mol%, the content of ZnO is 7-11 mol%, and the weight percentage of the additives in the manganese-zinc ferrite blank is 0.2-0.4%.

[0023] Optionally, the additive consists of V2O5 and SiO2 in a weight ratio of 1:(1-2).

[0024] (III) Beneficial effects

[0025] The beneficial effects of the present invention are:

[0026] The present invention provides a manganese-zinc ferrite laminated sintering method, wherein zirconium oxide powder with a specific composition ratio is mixed with water to obtain a mixed liquid, wherein the mass fraction of the zirconium oxide powder in the mixed liquid is 15% to 30%, and the mixed liquid is coated on the surface of the manganese-zinc ferrite. On the one hand, the mixed liquid can be stably maintained on the surface of the manganese-zinc ferrite, and on the other hand, it can effectively prevent the sticking of the blank and the deformation of the blank due to the melting of the manganese-zinc ferrite during the sintering process. On the third hand, due to the coating of the mixed liquid, the surface of the obtained finished product will form a rough and uneven concave and convex surface, that is, a rough surface, which is beneficial to improving the adhesion of the coating on the surface of the finished product and increasing the effective adhesion area. DETAILED DESCRIPTION

[0027] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation methods.

[0028] The present invention provides a manganese-zinc ferrite laminate sintering method, comprising the following steps:

[0029] S1. Mix zirconium oxide powder and water to obtain a mixed solution after mixing evenly; the mass fraction of zirconium oxide powder in the mixed solution is 15% to 30%, and the components of the zirconium oxide powder include zirconium oxide, yttrium oxide, magnesium oxide, polyvinyl alcohol, carboxymethyl cellulose, ammonium polyacrylate, sodium hexametaphosphate, plasticizer and lubricant.

[0030] Among the components of zirconium oxide powder, yttrium oxide and magnesium oxide can stabilize the crystal structure of zirconium oxide and improve the stability of zirconium oxide; polyvinyl alcohol and carboxymethyl cellulose as binders help to bond the zirconium oxide powder particles together during the molding process, thereby improving the handleability and stability of the zirconium oxide powder; ammonium polyacrylate and sodium hexametaphosphate as dispersants can effectively improve the dispersibility of zirconium oxide powder in liquid media and prevent agglomeration and precipitation; plasticizers are used to increase the plasticity of the material to facilitate the molding process of zirconium oxide powder; lubricants are used to reduce friction during the molding process and improve the surface quality of the product.

[0031] Preferably, the plasticizer is dibutyl phthalate. Preferably, the lubricant is stearic acid, graphite, etc.

[0032] Preferably, the components of the zirconium oxide powder, measured by mass percentage, include: 70% to 90% zirconium oxide, 5% to 15% yttrium oxide, 1% to 5% magnesium oxide, 1% to 5% polyvinyl alcohol, 0.5% to 3% carboxymethyl cellulose, 0.1% to 2% ammonium polyacrylate, 0.1% to 1% sodium hexametaphosphate, 0.5% to 3% plasticizer, and 0.1% to 2% lubricant.

[0033] The zirconium oxide powder having the above composition ratio is mixed with water to obtain a mixed liquid, wherein the mass fraction of the zirconium oxide powder in the mixed liquid is 15% to 30%. The mixed liquid is used to coat the surface of the manganese-zinc ferrite in S2. On the one hand, it can stably maintain on the surface of the manganese-zinc ferrite. On the other hand, it can effectively prevent the sticking and deformation of the blank caused by the melting of the manganese-zinc ferrite during the sintering process. On the third hand, due to the coating of the mixed liquid, the surface of the obtained finished product will form a rough and uneven concave and convex surface, that is, a rough surface. The rough surface is beneficial to improving the adhesion of the coating on the surface of the finished product and increasing the effective adhesion area.

[0034] Further preferably, the components of the zirconium oxide powder, measured by mass percentage, include: 75% to 86% zirconium oxide, 6% to 10% yttrium oxide, 1% to 3% magnesium oxide, 2% to 3% polyvinyl alcohol, 1.2% to 3% carboxymethyl cellulose, 0.9% to 1.5% ammonium polyacrylate, 0.6% to 1% sodium hexametaphosphate, 0.7% to 2% plasticizer, and 0.3% to 1.3% lubricant.

[0035] S2. neatly stack the manganese-zinc ferrite blanks on the support plate in one layer or more, wherein at least the upper surface of the manganese-zinc ferrite blanks in each layer is coated with the mixed liquid; then, the support plate and the manganese-zinc ferrite blanks carried thereon are placed in a sintering device for close-packed sintering to obtain a semi-finished product.

[0036] Preferably, the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid, and the coating method is: the manganese-zinc ferrite blanks are placed close to each other on the supporting plate, and after each layer is placed, a layer of the mixed liquid is brushed on the upper surface of the manganese-zinc ferrite blanks in that layer.

[0037] Optionally, the upper surface and side surface of the manganese-zinc ferrite blank in each layer are coated with a mixed liquid, and the coating method is: brushing the mixed liquid on the upper surface and side surface of the manganese-zinc ferrite blank to obtain a manganese-zinc ferrite blank coated with the mixed liquid, placing the manganese-zinc ferrite blanks coated with the mixed liquid close to each other on a setter plate, and stacking the manganese-zinc ferrite blanks neatly up and down in one or more layers. Among them, the side surface of the manganese-zinc ferrite blank is a surface used to connect the upper surface of the manganese-zinc ferrite blank and the lower surface of the manganese-zinc ferrite blank.

[0038] Optionally, all surfaces of the manganese-zinc ferrite blanks in each layer are coated with the mixed liquid, and the coating method is: immerse the manganese-zinc ferrite blanks in the mixed liquid and then take them out to obtain manganese-zinc ferrite blanks coated with the mixed liquid, place the manganese-zinc ferrite blanks coated with the mixed liquid close to each other on a supporting plate, and neatly stack the manganese-zinc ferrite blanks up and down in more than one layer.

[0039] Preferably, the close-packed sintering is divided into two stages, wherein in the first stage of sintering, the temperature is raised to 700-800°C at a heating rate of 5-10°C / min, and the sintering process is a fully open environment or an exhaust gas environment; in the second stage of sintering, the temperature is raised to 1300-1400°C at a heating rate of 80-90°C / min, and then kept warm for 280-330 minutes, and the sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment. In this way, in the first stage of sintering, the organic components are fully decomposed and the decomposed gases are discharged, and the zirconium oxide powder particles introduced into the mixed liquid are bonded together to form a sintering isolation film, which reduces adhesion during the sintering process and improves the surface quality of the product.

[0040] Sealed sintering can use inert gas (such as nitrogen) or reducing gas (such as hydrogen) as a protective gas to prevent the ferrite material from being oxidized at high temperatures. Sintering in a sealed environment means that the sintering furnace is a completely closed system, which can better control the atmosphere conditions in the furnace. The sealed environment helps prevent the outside air from entering and avoid oxidation or other unwanted chemical reactions.

[0041] Specifically, the shape of the manganese-zinc ferrite blank is a ring shape, an EE shape, a PQ shape or a pot shape.

[0042] Preferably, the components of the manganese-zinc ferrite blank include a main component and an additive; the main component includes Fe2O3, Mn3O4, NiO and ZnO, based on the amount of the main component, the content of Fe2O3 in the main component is 50-60mol%, the content of Mn3O4 is 10-16mol%, the content of NiO is 20-28mol%, the content of ZnO is 7-11mol, and the weight percentage of the additive in the manganese-zinc ferrite blank is 0.2-0.4%. Further preferably, the additive is composed of V2O5 and SiO2 in a weight ratio of 1:(1-2).

[0043] S3. After grinding the semi-finished product, it is cleaned and dried to obtain the manganese-zinc ferrite finished product.

[0044] S4, applying a coating layer to the surface of the finished manganese-zinc ferrite product, and then performing a curing treatment to obtain a coated ferrite.

[0045] Preferably, the curing temperature is 180-200° C., and the curing holding time is 10-16 minutes.

[0046] In this way, the obtained coated ferrite has a more reliable mechanical bite between the coating and the surface of the ferrite finished product, which improves the adhesion of the coating and solves the problem of poor adhesion of the coating and easy peeling of the coating.

[0047] Example 1

[0048] This embodiment provides a method for sintering a manganese-zinc ferrite laminate, comprising the following steps:

[0049] S1. Mix zirconium oxide powder and water to obtain a mixed solution after mixing evenly, wherein the mass fraction of zirconium oxide powder in the mixed solution is 20%.

[0050] The components of the zirconium oxide powder are calculated by mass percentage and include: 80% zirconium oxide, 9% yttrium oxide, 1.8% magnesium oxide, 2.5% polyvinyl alcohol, 2% carboxymethyl cellulose, 1% ammonium polyacrylate, 0.8% sodium hexametaphosphate, 1.5% dibutyl phthalate, and 1.2% stearic acid.

[0051] S2. neatly stack the annular manganese-zinc ferrite blanks on the support plate in more than one layer, and the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid. The coating method is: place the manganese-zinc ferrite blanks close to each other on the support plate, and after each layer is placed, brush a layer of mixed liquid on the upper surface of the manganese-zinc ferrite blank in this layer; then put the support plate and the manganese-zinc ferrite blanks carried on it into a sintering equipment for close-packed sintering. The close-packed sintering is divided into two stages. In the first stage of sintering, the temperature is increased to 750°C at a heating rate of 5°C / min, and the sintering process is an exhaust gas environment. In the second stage of sintering, the temperature is increased to 1350°C at a heating rate of 80°C / min, and then kept warm for 300 minutes. The sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment; a semi-finished product is obtained.

[0052] The components of the manganese-zinc ferrite blank include a main component and an additive; the main component includes Fe2O3, Mn3O4, NiO and ZnO, and based on the amount of the main component, the content of Fe2O3 in the main component is 55mol%, the content of Mn3O4 is 12mol%, the content of NiO is 25mol%, the content of ZnO is 8mol%, and the weight percentage of the additive in the manganese-zinc ferrite blank is 0.3%. Further preferably, the additive is composed of V2O5 and SiO2 in a weight ratio of 1:1.

[0053] The obtained semi-finished products have no adhesion or deformation, and the product size and performance are good, thereby improving the yield rate.

[0054] S3. After grinding the semi-finished product, it is cleaned and dried to obtain the finished manganese-zinc ferrite product. Take 5 samples of the same batch of the finished manganese-zinc ferrite product, and calculate the RSD (relative standard deviation) of the inner diameter, outer diameter and height dimensions <0.4%.

[0055] S4. Apply a coating layer to the surface of the finished manganese-zinc ferrite product, and then perform a curing treatment. The curing temperature is 200° C. and the curing and heat preservation time is 15 minutes to obtain a coated ferrite.

[0056] In accordance with GB / T 9286-2021, the coated ferrite sample was subjected to a cross-cut test. Six parallel scratches were cut on the surface of the film layer, and six parallel cuts were cut in a direction perpendicular to the six parallel scratches. The cross-cut spacing was 3 mm. After removing the loose smear debris, the adhesion level was visually compared with the six-level grading standard and was found to be level 3.

[0057] Example 2

[0058] This embodiment provides a method for sintering a manganese-zinc ferrite laminate, comprising the following steps:

[0059] S1. Mix zirconium oxide powder and water to obtain a mixed solution after mixing evenly, wherein the mass fraction of zirconium oxide powder in the mixed solution is 25%.

[0060] The components of the zirconium oxide powder are calculated by mass percentage and include: 85% zirconium oxide, 6% yttrium oxide, 1% magnesium oxide, 2% polyvinyl alcohol, 1.4% carboxymethyl cellulose, 1% ammonium polyacrylate, 0.7% sodium hexametaphosphate, 0.8% dibutyl phthalate, and 1% stearic acid.

[0061] S2. neatly stack the annular manganese-zinc ferrite blanks on the support plate in more than one layer, and the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid. The coating method is: place the manganese-zinc ferrite blanks close to each other on the support plate, and after each layer is placed, brush a layer of mixed liquid on the upper surface of the manganese-zinc ferrite blank in this layer; then put the support plate and the manganese-zinc ferrite blanks carried on it into a sintering equipment for close-packed sintering. The close-packed sintering is divided into two stages. In the first stage of sintering, the temperature is increased to 750°C at a heating rate of 10°C / min, and the sintering process is an exhaust gas environment. In the second stage of sintering, the temperature is increased to 1350°C at a heating rate of 90°C / min, and then kept warm for 300 minutes. The sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment; a semi-finished product is obtained.

[0062] The components of the manganese-zinc ferrite blank include a main component and an additive; the main component includes Fe2O3, Mn3O4, NiO and ZnO, based on the amount of the main component, the content of Fe2O3 in the main component is 50mol%, the content of Mn3O4 is 16mol%, the content of NiO is 27mol%, the content of ZnO is 7mol%, and the weight percentage of the additive in the manganese-zinc ferrite blank is 0.2%. Further preferably, the additive is composed of V2O5 and SiO2 in a weight ratio of 1:2.

[0063] The obtained semi-finished products have no adhesion or deformation, and the product size and performance are good, thereby improving the yield rate.

[0064] S3. After grinding the semi-finished product, it is cleaned and dried to obtain the finished manganese-zinc ferrite product. Take 5 samples of the same batch of the finished manganese-zinc ferrite product, and calculate the RSD (relative standard deviation) of the inner diameter, outer diameter and height dimensions <0.4%.

[0065] S4. Apply a coating layer to the surface of the finished manganese-zinc ferrite product, and then perform a curing treatment. The curing temperature is 200° C. and the curing and heat preservation time is 15 minutes to obtain a coated ferrite.

[0066] In accordance with GB / T 9286-2021, the coated ferrite sample was subjected to a cross-cut test. Six parallel scratches were cut on the surface of the film layer, and six parallel cuts were cut in a direction perpendicular to the six parallel scratches. The cross-cut spacing was 3 mm. After removing the loose smear debris, the adhesion level was visually compared with the six-level grading standard and was found to be level 3.

[0067] Example 3

[0068] This embodiment provides a method for sintering a manganese-zinc ferrite laminate, comprising the following steps:

[0069] S1. Mix zirconium oxide powder and water to obtain a mixed solution after mixing evenly, wherein the mass fraction of zirconium oxide powder in the mixed solution is 30%.

[0070] The components of the zirconium oxide powder are calculated by mass percentage and include: 75% zirconium oxide, 10% yttrium oxide, 3% magnesium oxide, 3% polyvinyl alcohol, 2.8% carboxymethyl cellulose, 1.4% ammonium polyacrylate, 0.9% sodium hexametaphosphate, 1.8% dibutyl phthalate, and 1.2% stearic acid.

[0071] S2. neatly stack the annular manganese-zinc ferrite blanks on the support plate in more than one layer, and the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid. The coating method is: place the manganese-zinc ferrite blanks close to each other on the support plate, and after each layer is placed, brush a layer of mixed liquid on the upper surface of the manganese-zinc ferrite blank in this layer; then put the support plate and the manganese-zinc ferrite blanks carried on it into a sintering equipment for close-packed sintering. The close-packed sintering is divided into two stages. In the first stage of sintering, the temperature is increased to 750°C at a heating rate of 10°C / min, and the sintering process is an exhaust gas environment. In the second stage of sintering, the temperature is increased to 1350°C at a heating rate of 90°C / min, and then kept warm for 300 minutes. The sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment; a semi-finished product is obtained.

[0072] The components of the manganese-zinc ferrite blank include a main component and an additive; the main component includes Fe2O3, Mn3O4, NiO and ZnO, based on the amount of the main component, the content of Fe2O3 in the main component is 60mol%, the content of Mn3O4 is 10mol%, the content of NiO is 20mol%, the content of ZnO is 10mol%, and the weight percentage of the additive in the manganese-zinc ferrite blank is 0.4%. Further preferably, the additive is composed of V2O5 and SiO2 in a weight ratio of 1:1.

[0073] The obtained semi-finished products have no adhesion or deformation, and the product size and performance are good, thereby improving the yield rate.

[0074] S3. After grinding the semi-finished product, it is cleaned and dried to obtain the finished manganese-zinc ferrite product. Take 5 samples of the same batch of the finished manganese-zinc ferrite product, and calculate the RSD (relative standard deviation) of the inner diameter, outer diameter and height dimensions <0.4%.

[0075] S4. Apply a coating layer to the surface of the finished manganese-zinc ferrite product, and then perform a curing treatment. The curing temperature is 200° C. and the curing and heat preservation time is 15 minutes to obtain a coated ferrite.

[0076] In accordance with GB / T 9286-2021, the coated ferrite sample was subjected to a cross-cut test. Six parallel scratches were cut on the surface of the film layer, and six parallel cuts were cut in a direction perpendicular to the six parallel scratches. The cross-cut spacing was 3 mm. After removing the loose smear debris, the adhesion level was visually compared with the six-level grading standard and was found to be level 3.

[0077] Example 4

[0078] This embodiment provides a method for sintering a manganese-zinc ferrite laminate, comprising the following steps:

[0079] S1. Mix zirconium oxide powder and water to obtain a mixed solution after mixing evenly, wherein the mass fraction of zirconium oxide powder in the mixed solution is 25%.

[0080] The components of the zirconium oxide powder are calculated by mass percentage and include: 70% zirconium oxide, 12% yttrium oxide, 4% magnesium oxide, 4% polyvinyl alcohol, 3% carboxymethyl cellulose, 1.8% ammonium polyacrylate, 0.9% sodium hexametaphosphate, 1.8% dibutyl phthalate, and 1.2% stearic acid.

[0081] S2. neatly stack the annular manganese-zinc ferrite blanks on the support plate in more than one layer, and the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid. The coating method is: place the manganese-zinc ferrite blanks close to each other on the support plate, and after each layer is placed, brush a layer of mixed liquid on the upper surface of the manganese-zinc ferrite blank in this layer; then put the support plate and the manganese-zinc ferrite blanks carried on it into a sintering equipment for close-packed sintering. The close-packed sintering is divided into two stages. In the first stage of sintering, the temperature is increased to 750°C at a heating rate of 10°C / min, and the sintering process is an exhaust gas environment. In the second stage of sintering, the temperature is increased to 1350°C at a heating rate of 90°C / min, and then kept warm for 300 minutes. The sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment; a semi-finished product is obtained.

[0082] The components of the manganese-zinc ferrite blank include a main component and an additive; the main component includes Fe2O3, Mn3O4, NiO and ZnO, based on the amount of the main component, the content of Fe2O3 in the main component is 60mol%, the content of Mn3O4 is 10mol%, the content of NiO is 20mol%, the content of ZnO is 10mol%, and the weight percentage of the additive in the manganese-zinc ferrite blank is 0.4%. Further preferably, the additive is composed of V2O5 and SiO2 in a weight ratio of 1:1.

[0083] The obtained semi-finished products have no adhesion or deformation, and the product size and performance are good, thereby improving the yield rate.

[0084] S3. After grinding the semi-finished product, it is cleaned and dried to obtain the finished manganese-zinc ferrite product. Take 5 samples of the same batch of the finished manganese-zinc ferrite product, and calculate the RSD (relative standard deviation) of the inner diameter, outer diameter and height dimensions <0.4%.

[0085] S4. Apply a coating layer to the surface of the finished manganese-zinc ferrite product, and then perform a curing treatment. The curing temperature is 200° C. and the curing and heat preservation time is 15 minutes to obtain a coated ferrite.

[0086] In accordance with GB / T 9286-2021, a cross-cut test was performed on the coated ferrite sample. Six parallel scratches were cut on the surface of the film layer, and six parallel cuts were cut in a direction perpendicular to the six parallel scratches. The cross-cut spacing was 3mm. After removing the loose smear debris, the adhesion level was visually compared with the six-level grading standard and was found to be level 2.

[0087] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0088] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0089] In the present invention, unless otherwise clearly specified and limited, when a first feature is “on” or “below” a second feature, it may be that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, when a first feature is “above”, “above” or “above” a second feature, it may be that the first feature is directly above or obliquely above the second feature, or it may simply mean that the first feature is higher in level than the second feature. When a first feature is “below”, “below” or “below” a second feature, it may be that the first feature is directly below or obliquely below the second feature, or it may simply mean that the first feature is lower in level than the second feature.

[0090] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "embodiment", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0091] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may alter, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A method for sintering a manganese-zinc ferrite laminate, characterized in that: The following steps are involved: S1. Mixing zirconium oxide powder and water to obtain a mixed solution after mixing evenly; the mass fraction of zirconium oxide powder in the mixed solution is 15% to 30%, and the components of zirconium oxide powder include zirconium oxide, yttrium oxide, magnesium oxide, polyvinyl alcohol, carboxymethyl cellulose, ammonium polyacrylate, sodium hexametaphosphate, plasticizer and lubricant; S2, stacking the manganese-zinc ferrite blanks neatly up and down in one layer or more on the setter plate, wherein at least the upper surface of the manganese-zinc ferrite blanks in each layer is coated with the mixed liquid; then placing the setter plate and the manganese-zinc ferrite blanks carried thereon into a sintering device for close-packed sintering to obtain a semi-finished product; S3, grinding the semi-finished product, cleaning and drying it to obtain a manganese-zinc ferrite finished product; Among them, the close-packed sintering is divided into two stages. In the first stage, the temperature is increased to 700-800°C at a heating rate of 5-10°C / min, and the sintering process is a fully open environment or an exhaust environment. In the second stage, the temperature is increased to 1300-1400°C at a heating rate of 80-90°C / min, and then kept warm for 280-330 minutes. The sintering atmosphere is pre-filled during the sintering process, and the sintering process is a sealed environment.

2. The method for sintering manganese-zinc ferrite laminates according to claim 1, characterized in that: The components of zirconium oxide powder are calculated by mass percentage and include: 70% to 90% zirconium oxide, 5% to 15% yttrium oxide, 1% to 5% magnesium oxide, 1% to 5% polyvinyl alcohol, 0.5% to 3% carboxymethyl cellulose, 0.1% to 2% ammonium polyacrylate, 0.1% to 1% sodium hexametaphosphate, 0.5% to 3% plasticizer, and 0.1% to 2% lubricant.

3. The method for sintering manganese-zinc ferrite laminates according to claim 1 or 2, characterized in that: The components of zirconium oxide powder are calculated by mass percentage and include: 75% to 86% zirconium oxide, 6% to 10% yttrium oxide, 1% to 3% magnesium oxide, 2% to 3% polyvinyl alcohol, 1.2% to 3% carboxymethyl cellulose, 0.9% to 1.5% ammonium polyacrylate, 0.6% to 1% sodium hexametaphosphate, 0.7% to 2% plasticizer, and 0.3% to 1.3% lubricant.

4. The method for sintering manganese-zinc ferrite laminates according to claim 1, characterized in that: In S2, the upper surface of the manganese-zinc ferrite blanks in each layer is coated with a mixed liquid, and the coating method is: the manganese-zinc ferrite blanks are placed closely to each other on the support plate, and after each layer is placed, a layer of the mixed liquid is brushed on the upper surface of the manganese-zinc ferrite blanks in that layer.

5. The method for sintering manganese-zinc ferrite laminates according to claim 1, characterized in that: In S2, all surfaces of the manganese-zinc ferrite blanks in each layer are coated with the mixed liquid, and the coating method is: immersing the manganese-zinc ferrite blanks in the mixed liquid and then taking them out to obtain manganese-zinc ferrite blanks coated with the mixed liquid, placing the manganese-zinc ferrite blanks coated with the mixed liquid close to each other on a supporting plate, and neatly stacking the manganese-zinc ferrite blanks up and down in more than one layer.

6. The method for sintering manganese-zinc ferrite laminates according to claim 5, characterized in that: Also includes: S4, applying a coating layer to the surface of the finished manganese-zinc ferrite product, and then performing a curing treatment to obtain a coated ferrite.

7. The method for sintering manganese-zinc ferrite laminates according to claim 1, characterized in that: In S2, the sintering temperature is 1300-1400°C, and the sintering time is 280-330 minutes.

8. The method for sintering manganese-zinc ferrite laminates according to claim 1, characterized in that: The shape of the manganese-zinc ferrite blank is ring-shaped, EE-shaped, PQ-shaped or pot-shaped.

9. The method for sintering manganese-zinc ferrite laminates according to claim 1, characterized in that: The components of the manganese-zinc ferrite blank include a main component and additives; The main components include Fe2O3, Mn3O4, NiO and ZnO. Based on the amount of the main components, the content of Fe2O3 in the main components is 50-60 mol%, the content of Mn3O4 is 10-16 mol%, the content of NiO is 20-28 mol%, the content of ZnO is 7-11 mol%, and the weight percentage of the additives in the manganese-zinc ferrite blank is 0.2-0.4%.

10. The method for sintering manganese-zinc ferrite laminates according to claim 9, characterized in that: The additive is composed of V2O5 and SiO2 in a weight ratio of 1:(1-2).

Citation Information

Patent Citations

  • Sintering method for high saturated flux density MnZn ferrite

    CN101090016A

  • Sand glue for preventing blank from adhesion, preparation and application thereof

    CN101555132A

  • Superimposition sintering technology of manganese zinc ferrite

    CN102491759A

  • Preparation method of layered structure ceramic ring for mechanical sealing

    CN111825454A

  • Manufacturing process of special-shaped ferrite magnetic core

    CN114005669A